Over-expression of gibberellin-20 oxidase gene in kenaf (Hibiscus cannabinus L) for increased fiber quality - Withanage, Samathi Priyanka (2012)
Kenaf (Hibiscus cannabinus L.) is a multipurpose herbaceous crop belongs to the family Malvaceae. It is one of the potential alternatives of natural fibers for biocomposite production including pulp and paper. Kenaf generally grows very fast in the tropics. The kenaf stem consists of long bast (represents 34 - 38% of the stem) and short core fibers (represents 62 - 66% of the stem). The success of the kenaf fiber used industries has relied upon its high yield per hectare and, the quality and quantity of its bast and core fibers. Current data on the yield of kenaf fibers shows that there is still plenty of room for improvement. Therefore, the development of improved kenaf planting materials is one of the areas where more research should be focused upon. Ideally, longer fiber length indicated by short core fiber and higher cellulose content are required for high quality kenaf fiber. In plants, gibberellic acid (GA)which is an important plant hormone influences the structural development of a plant and its organs. The hormone stimulates cell division and elongation, and promotes transition of vegetative to reproductive growth. Therefore, in this study, it is hypothesized that by increasing the active GA, the fiber length and cellulose content (biomass) of kenaf would be increased. The hypothesis was tested by evaluating the effects of over expression of gibberellin 20 oxidase (GA20ox) gene, one of the key enzymes in GA biosynthetic pathway in kenaf. Two forms of GA 20 oxidase gene i.e. a gene with intron (AtGA20ox-In) and a gene without the intron (AtGA20ox-cDNA) were isolated from Arabidopsis thaliana ecotype Colombia and overexpressed in kenaf under the control of the double CaMV 35S promoter. This was followed by in planta (in vitro) transformation into the V36 (intermediate flowering) and G4 (late flowering) varieties of kenaf. The putative higher levels of bioactive GA (0.3-1.52 ng/g fresh weight) were chosen for further characterization of their morphological and biochemical traits including vegetative and reproductive growth, fiber dimensions and chemical composition. Different levels of GA20ox expression were observed in the transgenic lines ranging from 2 to 39 fold increases of the transcripts level. The expression level was correlated positively with the production of bioactive GA1 and GA4. Various types of phenotypes as short non flowering, short early flowering, normal flowering and tall non flowering were observed among the transgenic lines in both of the varieties transformed. Two transgenic lines (V36-2 and V36-3) out of four lines produced high levels of GAs (1.43 and 1.23 ng/g fresh weight) flowered at 7th week. It was considered as very early compare to untransformed plants which flowered at 13th week. However, these lines were unable to complete their reproductive phase resulting in poor seed production. The other two lines (G4-5 and G4-7) showed impaired vegetative and reproductive growth characterizing by lack of reproductive phase. It is speculated that the lines might be subjected to gibberellins homeostasis where those with normal levels of GAs (around 0.3ng/g fresh weight) grew phenotypically normal, whereas the lines that produced slightly higher concentrations of GAs (0.32-0.52 ng/g fresh weight) produced better vegetative growth which exhibited delayed in flowering or failed in initiating flowering. Positive impact of gibberellins on biochemical composition, fiber dimensions and their derivative values of kenaf was demonstrated in some lines of the transgenic transformants over expressing AtGA20ox gene were screened for hygromycin B resistance and confirmed by PCR and Southern blot analysis. The transgene transcripts of the transgenic kenaf were analyzed by real time PCR, and the levels of bioactive GA1 and GA4 were determined by GC-MS analysis. The lines that showed kenaf including the increased cellulose content of 91% and increased fiber length of 3.22 mm for bast fiber and 1.1mm for core fiber. It has been noticed that the levels of bioactive GA1 and GA4 have influence in determining the vegetative growth and reproductive development of kenaf. But it required a further detailed study to confirm the critical level of this bioactive GA. This study confirmed the hypothesis that GA is extremely important for increasing the length of the kenaf fiber. The findings can be used as a basis for further improving the quality and quantity of kenaf in the industry.